Empowering Teachers, Triggering Change: A Case Study of Teacher Training through Action Research - Ana Halbach (Estudios sobre Educación, 2016)
The present article sets out to validate small-scale research projects as a tool to foster the integration of theory and practice as well as the development of a refl ective mindset in trainees in teacher training courses. This case study of the process followed by an experienced teacher carrying out research as part of a Master’s degree in Teaching English traces the student’s learning during her research process through an analysis of her interactions, both oral and written, with the thesis supervisor, as well as of the materials created for the pedagogical intervention planned and the data collection carried out as part of the action research process. This reconstruction of the trainee’s developing understanding while working on her MA thesis reveals that learning does take place and is brought about by a mixture of different factors, such as the relation established between the theoretical concepts studied in the program and the actual teaching practice, the detachment brought about by the need to collect data and the interaction with the supervisor. Carrying out a research project also helps the trainee to reflect on her own practice, and thus establish a reflective mindset.